CircCRIM1 promotes ovarian cancer progression by working as ceRNAs of CRIM1 and targeting miR-383-5p/ZEB2 axis - Yuping Du; Xin Liu; Song Zhang; Shuo Chen; Xue Guan; Qianhui Li; Xi Chen; Yang Zhao (BMC, 2021)
Abstract Background Ovarian cancer is the leading cause of death in patients with gynecologic cancer, and circular RNAs (circRNAs) are involved in cancer progression. However, there are limited studies on the roles of circRNAs in ovarian cancer. Methods We designed divergent and convergent primers, used sanger sequencing and RNase R digestion to verify the source of circCRIM1. We detected the expression of circCRIM1 and its parental gene cysteine rich transmembrane BMP regulator 1 (CRIM1) in ovarian cancer and normal ovarian samples via qRT-PCR. MTT viability assay, apoptosis assay, wound healing assay and invasion assay were used to investigate the function of circCRIM1 and CRIM1 in ovarian cancer cell lines OVCAR3 and CAOV3. Mice xenografts experiment was performed. Bioinformatics predicted the microRNAs that bond with circCRIM1 and CRIM1, and dual luciferase reporter system confirmed it. Rescue experiments of microRNAs mimics transfection on the basis of circCRIM1 over-expression were carried out to uncover the mechanism by which circCRIM1 played cancer-promoting roles in ovarian cancer. Results CircCRIM1 was derived from CRIM1 by back-splicing. CircCRIM1 and CRIM1 had higher expression in ovarian cancer than in normal ovarian tissues, and both of them promoted ovarian cancer progression in vitro. In vivo circCRIM1 promoted the growth of tumors. CircCRIM1 and CRIM1 had a positive correlation relationship in the same cohort of ovarian cancer tissues. Bioinformatics predicted and dual luciferase assay confirmed circCRIM1 and CRIM1 bond with miR-145-5p, and circCRIM1 bond with miR-383-5p additionally. CircCRIM1 positively affected the expression of CRIM1. After circCRIM1 was over-expressed, miR-145-5p mimics transfection reversed the expression of CRIM1. Western blot discovered circCRIM1 positively affected the expression of zinc finger E-box binding homeobox 2 (ZEB2). Rescue experiments found miR-383-5p mimics reversed ZEB2 expression and the cancer-promoting effects of circCRIM1. Conclusions CircCRIM1 bond with miR-145-5p to work as competing endogenous RNA (ceRNA) of CRIM1, and circCRIM1 bond with miR-383-5p to improve the expression of ZEB2 in ovarian cancer. CircCRIM1 and CRIM1 promoted the ovarian cancer progression and supplied a novel insight into the researches of ovarian cancer.